Characterization of some bioactive compounds and physicochemical properties of grape varieties grown in Turkey: thermal degradation kinetics of anthocyanin - Karasu, Salih; Baslar, Mehmet; Karaman, Safa; Kilicli, Mahmut; Us, Ahmet Abdullah; Yaman, Hasan; Sagdic, Osman (Tubitak Scientific & Technological Research Council Turkey, 2016)
In the present study, five different grapes varieties grown in Turkey were comprehensively characterized in terms of physicochemical properties, total bioactive content, antiradical activity, and volatile sugar compounds. Thermal degradation kinetics of anthocyanin in the selected grape varieties were also analyzed. All the bioactive compounds and antiradical activity varied depending on variety and grape part (skin, pulp, or seed). Higher amounts of total phenolics, total flavonoids, anthocyanin, and antiradical capacity were obtained from seeds. Fifty-nine volatile compounds were observed in the grape varieties. Terpenoid compounds were determined to be the predominant aroma compounds, of which limonene and citral had the highest content, with values ranging from 46.269% to 77.209% and from 3.327% to 12.371%, respectively. The half-life period of anthocyanin degradation in grapes with a temperature range of 60 to 90 degrees C ranged from 3.51 to 34.65, 3.26 to 35.50, 2.76 to 40.77, and 3.02 to 43.31 for Antep Karasi, Efes, Kara Dimrit, and Cardinal Red, respectively. Efes and Cardinal had the greatest amount of bioactive compounds among the grape varieties.
Keywords: Grape; Antep Karasi; Efes; Kara Dimrit; phenolic; ANTIOXIDANT PROPERTIES; TABLE GRAPE; AROMA; CULTIVARS; BLACKBERRY; CAPACITY; SEED; Agriculture; Forestry